Coumarin Glycosides and Iridoid Glucosides with Neuroprotective Effects from Hydrangea paniculata - Shi, Jing; Li, Chuang-Jun; Yang, Jing-Zhi; Yuan, Yu-He; Chen, Nai-Hong; Zhang, Dong-Ming (Planta Medica, 2012)
Five new coumarin glycosides, umbelliferone 7-O-sophoroside (1), umbelliferone 7-O-β-D-glucopyranosyl(1 → 3)-β-D-glucopyranoside (2), umbelliferone 7-O-β-D-glucopyranosyl(1 → 3)-[β-D-apiofuranosyl(1 → 6)]-β-D-glucopyranoside (3), umbelliferone 7-O-β-D-glucopyranosyl(1 → 2)-β-D-apiofuranosyl(1 → 6)-β-D-glucopyranoside (4), and umbelliferone 7-O-β-D-glucopyranosyl(1 → 5)-β-D-apiofuranosyl(1 → 6)-β-D-glucopyranoside (5), and two new iridoid glucosides, 7-O-E-isoferuloyl loganic acid (6) and 7-O-β-D-glucopyranosyl loganin (7), together with eight known compounds (8–15) were isolated from the stems of Hydrangea paniculata. Their structures were established by spectroscopic analysis and chemical methods. At 10 µM, compounds 1, 3, 5, 6, 8, 9, and 13 showed neuroprotective effects against serum deprivation-induced PC12 cell damage.
Keywords: Hydrangea paniculata; Saxifragaceae; coumarin glycosides; iridoid glucosides; neuroprotective effects